2021
DOI: 10.1002/cnma.202100315
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐Mediated Synthesis of Colloidal 2D Halide Perovskite Nanoplatelets

Abstract: Colloidal synthesis of two‐dimensional lead halide perovskite nanoplatelets (2D LHP NPLs) with a general formula of L2[APbX3]n−1PbX4 has been widely performed by using hot‐injection or ligand assisted reprecipitation methods. Herein, for the first time, we report on seed‐mediated synthesis of two and three monolayers (n=2, 3) lead halide perovskite nanoplatelets without using A‐site cation halide salt (AX; A=Cesium, methylammonium, formamidinium and, X=Cl, Br, I) and long chain alkylammonium halide salts (LX; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 57 publications
(89 reference statements)
2
13
0
Order By: Relevance
“…Particle size distributions of L 2 [GAPbI 3 ]­PbI 4 , L 2 [GA 0.5 FA 0.5 PbI 3 ]­PbI 4 , and L 2 [FAPbI 3 ]­PbI 4 NCs are shown in Figure f–h, respectively, and they are very close to each other, around 3.5 nm. In our previous work, we demonstrated that the size of the PbI 2 seeds used in the seed-mediated synthesis is around 3 nm . In fact, the size of the LHP products obtained in this study is very close to the size of the seeds shown in our previous study.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Particle size distributions of L 2 [GAPbI 3 ]­PbI 4 , L 2 [GA 0.5 FA 0.5 PbI 3 ]­PbI 4 , and L 2 [FAPbI 3 ]­PbI 4 NCs are shown in Figure f–h, respectively, and they are very close to each other, around 3.5 nm. In our previous work, we demonstrated that the size of the PbI 2 seeds used in the seed-mediated synthesis is around 3 nm . In fact, the size of the LHP products obtained in this study is very close to the size of the seeds shown in our previous study.…”
Section: Resultssupporting
confidence: 83%
“…In this study, we colloidally synthesized 2D RP L 2 [GA x FA 1– x PbI 3 ]­PbI 4 (0 ≤ x ≤ 1) ( n = 2) NCs as schematically illustrated in Figure . We indeed used the seed-mediated synthesis of perovskite NCs . Different from the previous study, in this study, we used 0.4 M oleylammonium iodide (OLAM-I) in oleylamine (OLAM) instead of using OLAM.…”
Section: Resultsmentioning
confidence: 99%
“…This can be achieved by controlling the thickness of the Br-and I-based NPls rather than having a mixed halide composition. 378,407,[409][410][411]414,[463][464][465][466][467][468][469][470][471] The OAm/OAc pair has been successfully applied in the synthesis of halide perovskite NPls. 407,410,411,433,468 It was found that the ratio of OAm/OAc together with the reaction temperature plays a critical role in the formation of NPl.…”
Section: Cspbx 3 Nanowiresmentioning
confidence: 99%
“…As shown in Figure a, new excitonic absorption peaks at ∼2.88 eV appear along with the absorption of MAPbBr 3 at ∼2.42 eV in the UV–vis spectrum of the core–shell NCs, indicating the formation of layered perovskite ( n = 2) that is composed of corner-shared [(MA + )­Pb 2 Br 7 ] 2– bilayers separated by the interdigitated organic cations. , The core–shell NCs exhibit a similar PL pattern (Figure a) and a comparable film PLQY (54%) to the MAPbBr 3 NCs. The high-resolution TEM (HRTEM) images (Figure b,c) demonstrate the core–shell structure of the as-prepared NCs, which exhibits a similar spherical morphology with the bare 3D MAPbBr 3 NCs (Figure S2) and a representative lattice spacing of 0.29 nm assigned to the (200) plane. , However, because of the large amount of the organic part in the low-dimensional perovskite shell and the structural instability at high magnification, it is difficult to observe lattice spacing in the shell. ,,, Additionally, the XRD pattern (Figure S3) presents diffraction peak at 9.8° corresponding to the (040) plane of layered perovskite with n = 2, , in addition to the typical diffraction peaks of the { k 00} family at 15.02 and 30.19° of the cubic 3D MAPbBr 3 NCs. These results suggest the formation of NCs with a low-dimensional shell and a 3D core. Different from core–shell NCs fabricated by epitaxial growth (such as CdSe/CdS, etc.…”
Section: Resultsmentioning
confidence: 94%
“…38,39 However, because of the large amount of the organic part in the low-dimensional perovskite shell and the structural instability at high magnification, it is difficult to observe lattice spacing in the shell. 14,37,40,41 Additionally, the XRD pattern (Figure S3) presents diffraction peak at 9.8°c orresponding to the (040) plane of layered perovskite with n = 2, 42,43 in addition to the typical diffraction peaks of the {k00} family at 15.02 and 30.19°of the cubic 3D MAPbBr 3 NCs. These results suggest the formation of NCs with a lowdimensional shell and a 3D core.…”
Section: ■ Results and Discussionmentioning
confidence: 99%